2017
DOI: 10.1051/0004-6361/201730449
|View full text |Cite
|
Sign up to set email alerts
|

The implications of the surprising existence of a large, massive CO disk in a distant protocluster

Abstract: Itis not yet known if the properties of molecular gas in distant protocluster galaxies are significantly affected by their environment as galaxies are in local clusters. Through a deep, 64 hours of effective on-source integration with the Australian Telescope Compact Array (ATCA), we discovered a massive, M mol = 2.0 ± 0.2 × 10 11 M , extended, ∼40 kpc, CO(1-0)-emitting disk in the protocluster surrounding the radio galaxy, MRC 1138−262. The galaxy, at z CO = 2.1478, is a clumpy, massive disk galaxy, M * ∼ 5 ×… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 146 publications
(265 reference statements)
11
88
0
Order By: Relevance
“…Figure 13 displays the relation between the apparent CO luminosities, L ′ CO(1−0) , and the width (∆V) of the CO emission lines for the sources presented in this work and a compilation of high-z lensed and unlensed SMGs, as well as local ULIRGs from the literature (see figure caption for details and references). This relationship has already been presented and discussed in previous studies (e.g., Harris et al 2012;Bothwell et al 2013;Carilli & Walter 2013;Aravena et al 2016;Yang et al 2017;Dannerbauer et al 2017;Isbell et al 2018). Figure 13 includes CO measurements of ∼160 galaxies in total; it should be noted that none of the gravitationally lensed sources in this plot was corrected for lensing magnification.…”
Section: Co Luminosities and The L ′supporting
confidence: 74%
“…Figure 13 displays the relation between the apparent CO luminosities, L ′ CO(1−0) , and the width (∆V) of the CO emission lines for the sources presented in this work and a compilation of high-z lensed and unlensed SMGs, as well as local ULIRGs from the literature (see figure caption for details and references). This relationship has already been presented and discussed in previous studies (e.g., Harris et al 2012;Bothwell et al 2013;Carilli & Walter 2013;Aravena et al 2016;Yang et al 2017;Dannerbauer et al 2017;Isbell et al 2018). Figure 13 includes CO measurements of ∼160 galaxies in total; it should be noted that none of the gravitationally lensed sources in this plot was corrected for lensing magnification.…”
Section: Co Luminosities and The L ′supporting
confidence: 74%
“…At 1.4 GHz (rest-frame ∼ 5 GHz), a subset of our SMGs are spatially resolved on ∼ 1.3 ′′ (r 1.4 GHz ∼ 10 kpc) scales, in good agreement both with previously measured 1.4 GHz SMG sizes in the Lockman Hole field obtained with high-resolution (∼ 0.2 ′′ ) imaging from the Multi-Element Radio-Linked Interferometer Network (MER-LIN; Biggs & Ivison 2008), and with the stellar disk sizes of SMGs in the ECDFS field measured via near-IR imaging with HST (Aguirre et al 2013;Chen et al 2015). Moreover, observations of cold gas tracers in SMGs show the ISM of SMGs to be extended on scales of 10 kpc Thomson et al 2012;Emonts et al 2016;Dannerbauer et al 2017;Gullberg et al 2018).…”
Section: The Multi-frequency Sizes Of Smgssupporting
confidence: 72%
“…For example, detected CO(3−2) line emission in seven star-forming galaxies associated with the protocluster 4C23.56 at z = 2.49 and derived a median SFE consistent with the reference sample (although different results have been reported in the same structure, as discussed below; Tadaki et al 2019). Dannerbauer et al (2017) detected an extended CO(1 − 0) emitting disk in a proto-cluster member galaxy at z ≈ 2.15, whose gas properties and SFR follow the same relation as normal field galaxies. Similarly, Darvish et al (2018) used ALMA dust continuum observations to investigate the role of environmental density on the molecular gas content in a large sample of ∼ 400 massive (M ⋆ 10 10 M ⊙ ) galaxies within z ≈ 0.5 − 3.5, where the density was estimated by the projected surface density of galaxies over different redshift slices, and concluded that the SFE is independent of galaxy overdensity.…”
Section: The Star Formation Efficiencymentioning
confidence: 71%
“…The work by Bouwens et al (2016) is, however, based on observations a factor of ∼ 3x deeper. Dannerbauer et al 2017), and starvation (when gas accretion is stopped).…”
Section: Environmental Quenchingmentioning
confidence: 99%